(untitled) (Journal of Science & Technology, 2021)
Sustainable living has its genesis in comfortable, cost-effective and resource efficient spaces, created by using nature based solutions. Each era is known to be credited with distinct challenges to human living. We need to learn how communities in that particular era overcame those challenges. With fast advancement in science and rapidly changing technologies we are becoming essentially mechanical, creating building options with large footprints expanding both horizontally and vertically. In the process buildings are becoming major consumers of energy and resources besides generators of waste, asking for more and more energy to be produced and consumed. There is an urgent need to pause, stop for a moment, think and integrate all our traditional wisdom and good practices for a creating a sustainable built environment. Corona, a smallest virus has made mankind helpless and handicapped for months together. It has taught us, for sure some good healthy behavioral practices and positive lessons that can make our lives more sustainable. Sustainability has its genesis in adopting nature based solutions for planning and designing built environment. This research paper deals with making a case for adopting good practices, based on traditional wisdom with special focus on tribal communities ,that can lead to creating sensible and sustainable options for human living.